The Relationship between Engineer Skill Ability towards Manufacturing Employer’s Satisfaction: A Fundamental Study - Saleh, Hasan (Journal of Technical Education and Training, 2020)
The purpose of this study is to investigate the employers’ satisfaction with the skill of engineering graduates in Malaysia. This study attempt to investigate the relationship between engineering skill ability towards manufacturing employer’s satisfaction. Implicitly, we do not know the most demanded and essential skill that needed toward employer satisfaction nowadays. The method used in this study is quantitative method where questionnaire forms distribute to the company representatives. This study uses 195 survey questionnaires distributed to manufacturing senior managers in Melaka, Negeri Sembilan and Pulau Pinang. Statistical Package for Social Science (SPSS) software version 22.0 has been used to extract the data needed from the survey. Findings indicate that employers are satisfied with the skill equipped with the engineering graduates and show that fundamental general skill (FGS) and engineering skills (EgS) are the most essential element to ensure employer’s satisfaction followed closely by other skills. The results offer important practical implication for engineering graduates to succeed in employability. Proper skills are important in the race to gain employer’s satisfaction in terms of necessary skills needed in engineering graduates. It is hoped that these data can be an essential reference for engineering graduates to prepare themselves to enter the working environment especially in this challenging economic situation.